2013
DOI: 10.1016/j.fm.2012.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of geraniol metabolism during fermentation

Abstract: Geraniol produced by grape is the main precursor of terpenols which play a key role in the floral aroma of white wines. We investigated the fate of geraniol during wine fermentation by Saccharomyces cerevisiae. The volatile compounds produced during fermentation of a medium enriched with geraniol were extracted by Stir-bar sorptive extraction and analysed by GC-MS. We were able to detect and quantify geranyl acetate but also citronellyl- and neryl-acetate. The presence of these compounds partly explains the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 34 publications
3
56
2
1
Order By: Relevance
“…S. cerevisiae harbors two old yellow enzymes (OYE2 and OYE3) which catalyze the flavin-dependent, stereospecific reduction of α,β-unsaturated double bonds (Williams and Bruce, 2002). Previous studies concluded that OYE2 (but not OYE3) is involved in direct α,β-unsaturated monoterpenol reduction and is a target for increasing flux through the strictosidine pathway (Steyer et al, 2013). Other reports however, indicated that OYEs cannot reduce α,β-unsaturated alcohols, and that substrate reduction must proceed through activated α,β-unsaturated carbonyl intermediates (Brenna et al, 2012; Lonsdale and Reetz, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S. cerevisiae harbors two old yellow enzymes (OYE2 and OYE3) which catalyze the flavin-dependent, stereospecific reduction of α,β-unsaturated double bonds (Williams and Bruce, 2002). Previous studies concluded that OYE2 (but not OYE3) is involved in direct α,β-unsaturated monoterpenol reduction and is a target for increasing flux through the strictosidine pathway (Steyer et al, 2013). Other reports however, indicated that OYEs cannot reduce α,β-unsaturated alcohols, and that substrate reduction must proceed through activated α,β-unsaturated carbonyl intermediates (Brenna et al, 2012; Lonsdale and Reetz, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, saturated shunt products represent a non-recoverable loss in carbon which severely limits overall iridoid yields. While several reports have described the reduction of the double bonds in monoterpene pathway intermediates by yeast (Gramatica et al, 1982; King and Richard Dickinson, 2000; Steyer et al, 2013), the exact mechanism has remained unresolved particularly with regard to crosstalk between exogenous biosynthetic enzymes (GOR and ISY) and endogenous yeast enzymes. However the low benchmark titers of 8-hydroxygeraniol 2 achieved to date (5.3 mg/L) (Campbell et al, 2016), in combination with the obscured mechanistic details of shunt product formation have significantly limited the reconstitution of nepetalactol 3 production and overall MIA pathway engineering in yeast.…”
Section: Introductionmentioning
confidence: 99%
“…Geraniol is metabolized by yeast primarily through esterification to form geranyl acetate and through reduction to form citronellol (37). Deletions of ATF1, encoding an alcohol acetyltransferase, and OYE2, encoding an NADPH oxidoreductase, are reported to attenuate these reactions (37). Thus, we deleted OYE2 and ATF1 in strain 1 to create strain 2.…”
Section: Significancementioning
confidence: 99%
“…The catalytic source of citronellol biosynthesis remains, as yet, unclear. In yeast, the enzyme (old yellow enzyme) responsible for the reduction of geraniol has been identified (Steyer et al, 2013). We deleted its homolog, nemA, but did not observe a decrease in citronellol production (Tashiro, M., unpublished data).…”
Section: Discussionmentioning
confidence: 98%